Innovative Centers — Pomorskie Region Case Study - Przybyłowski, Adam; Królikowska, Katarzyna (Regional Barometer. Analyses & Prognoses, 2018)
At present innovation is a very important element of modern economy that is developing thanks to investment in research and development and also on the basis of technology transfer and commercialization of knowledge. Currently there are more and more institutions in Poland aimed at supporting entrepreneurs in pursuit of innovation. The purpose of the publication is to show the innovation centers on the example of institutions operating in the Tri-City (Gdańsk, Gdynia, Sopot). The hypothesis that these centers stimulate the innovative activities of entrepreneurs and business initiates has been confirmed. The method used in the work was survey and a research tool — questionnaire survey. The results show that the most important factor is the convenient location and the possibility of establishing new, valuable business contacts. Such favorable and noticeable opinions among the staff of the centers prove that they fulfill their role and are able to stimulate the Polish economy, becoming more and more competitive thanks to the development of science and technology.